Analisis Implementasi Metode Demonstrasi Dalam Pembelajaran Pendidikan Agama Islam Kelas X Di SMA Negeri Darussholah Singojuruh - Muttaqin, Ahmad Izza (Fikroh: Jurnal Pemikiran dan Pendidikan Islam, 2021)
This study aims to explain the implementation of the demonstration method in learning Islamic religious education class X at SMA Negeri Darussholah Singojuruh. This research uses a descriptive qualitative approach. Methods of data collection using non-participant observation methods, semi-structured interviews and documentation. The subjects of this study were the principal, Islamic education teachers and class X MIA students. The data validity was done by using data triangulation technique and source triangulation technique. Data analysis includes data collection (data collection), data reduction (data reduction), data display (data presentation) and conclusion drawing / verification. The result of this research is that in teaching Islamic Education the teacher uses the demonstration method by applying three stages, namely preparation, implementation and evaluation of learning. Preparation for learning the teacher prepares learning tools, formulates goals to be achieved, prepares the necessary tools or media and estimates the time that will be used in learning. The supporting factors are the presence of professional teachers, media, adequate facilities and infrastructure, making it easier for students to understand what is being learned..